Protective effect against gastric mucosa injury of a sulfated agaran from Acanthophora spicifera. (1st June 2021) - Pereira Júnior, Lindauro C.; Nascimento, Fernando G.; Oliveira, Samara R.B.D.; Lima, Glauber C.; Chagas, Francisco Diego S.; Sombra, Venicios G.; Feitosa, Judith P.A.; Soriano, Eliane M.; Souza, Marcellus H.L.P.; Zocolo, Guilherme J.; Silva, Lorena M.A.; de Paula, Regina C.M.; et al.
Graphical abstract: Highlights: Polysaccharide from Acanthophora spicifera (PAs) is an agar-type polysaccharide. PAs possesses a high sulfate content. PAs reduces the oxidative stress and enhances defense mechanisms of the gastric mucosa. Abstract: In this study, a polysaccharide from marine alga Acanthophora spicifera (PAs) was isolated and structurally characterized. Its protective potential against chemically-induced gastric mucosa injury was evaluated. The gel permeation chromatography experiments and spectroscopy spectrum showed that PAs is a sulfated polysaccharide with a high molecular mass (6.98 × 10 5 g/mol) and degree of sulfation of 1.23, exhibiting structural characteristic typical of an agar-type polysaccharide. Experimental results demonstrated that PAs reduced the hemorrhagic gastric injury, in a dose-dependent manner. Additionally, PAs reduced the intense gastric oxidative stress, measured by glutathione (GSH) and malondialdehyde (MDA) levels. PAs also prevented the reduction of mucus levels adhered to the gastric mucosa, promoted by the aggressive effect of ethanol. In summary, the sulfated polysaccharide from A. spicifera protected the gastric mucosa through the prevention of lipid peroxidation and enhanced the defense mechanisms of the gastric mucosa, suggesting as a promising functional food as gastroprotective agent.